Analisis Risiko Pendistribusian Barang pada PT Pos Indonesia dengan Metode SCOR (Studi Kasus: Kantor Pos Pusat Bandung) - Syahputro, Agung; Ahmadi, Hilmi; Sabana, Mutiara; Mayldiana, Friska (ARZUSIN, 2024)
This research was conducted on a case study of a postal and logistics service company involving the Indonesian Post Office entity, courier services, and postal officers. The problems faced are risks during the distribution of goods from customers that cause delays in distribution. Evaluation of the delivery system is needed to maintain customer satisfaction. The study's overarching goal is to map out ways to reduce supply chain risks by identifying potential threats and quantifying their severity throughout product delivery via the Bandung Central Post Office. Companies may use the Supply Chain Operations Reference (SCOR) technique and a House of Risk (HoR) to assess failures and predict them in the supply chain. This study provides a framework for identifying possible risks throughout the supply chain. Direct observation and review of the literature were the methods used to gather data.